(untitled) (Economic and Political Thought, 2013)
The research: (1) embraces peculiarities of the current EU foreign policy towards Ukraine; (2) enumerates and analyzes documents, agreements and treaties which establish the frameworks for this policy; (3) discovers the impact of human rights issues on shaping and conducting this policy. Based on the criminal trials against opposition leaders, the analysis is provided to establish to what extent the human rights violation in Ukraine can worsen the relations between Kyiv and Brussels in the current context. As a result, several key factors which can alter the EU foreign policy towards Ukraine are pointed out.